Persepsi Pengguna Terhadap Kemanfaatan dan Kemudahan Penggunaan Aplikasi Sistem Informasi Baru di STIE SBI - Surawan Setyo Budi (EBBANK, 2016)
In order to improve monitoring, guidance and control at universities, since 2014 the government has imposed a new application called FEEDER system that can be used to submit semi-annual reports of academic activities by universities to DIKTI. This study aims to determine the factors that affect user satisfaction of the system by using four factors: the quality of information systems, the quality of information, quality reliability and safety qualities. Respondents in this research were 106 people carriers Kopertis PTS entire region V. Methods of data collection using questionnaires, measuring instruments with 5-point Likert scale on test validity and reliability and analyzed using regression analysis. The results of the four factors were examined using "ease" as a variable interverning have found that the quality of information systems and quality that affect the reliability of the system user satisfaction.